2018
DOI: 10.1111/crj.12779
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of drug‐resistant extrapulmonary tuberculosis

Abstract: The prevalence of DR-EPTB was high in patients who had concomitant PTB. Although the prevalences of rifampicin- and multidrug-resistant TB were low in isolated EPTB, the prevalence of isoniazid-resistant TB remained high. Therefore, drug susceptibility testing should be performed in EPTB patients, especially those who carry the aforementioned risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 23 publications
1
25
2
Order By: Relevance
“…Previous studies reported from India indicated a higher MDR-TB cases proportion than our findings [25,27,28]. In contrast, two studies from Korea [26,35] one study from Thailand [24], and one study from Ethiopia [23] have reported a lower MDR-TB proportion than our findings. The possible reasons for the difference between our findings and previous studies results could be the non-adherence level, lost to follow up, poor drug supply chain management, and quality of drugs used [36].…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Previous studies reported from India indicated a higher MDR-TB cases proportion than our findings [25,27,28]. In contrast, two studies from Korea [26,35] one study from Thailand [24], and one study from Ethiopia [23] have reported a lower MDR-TB proportion than our findings. The possible reasons for the difference between our findings and previous studies results could be the non-adherence level, lost to follow up, poor drug supply chain management, and quality of drugs used [36].…”
Section: Discussioncontrasting
confidence: 97%
“…In the current study resistance to INH was the most frequent. This proportion is higher than the earlier result reported from Ethiopia [23] and Thailand [24]. However, our finding is similar to the results reported in India [25] and South Korea [26].…”
Section: Discussionsupporting
confidence: 75%
“…Out of 85 M. tuberculosis isolates included in this study, one (3.1%) was multidrug resistant. This proportion is lower than the earlier results reported from Thailand, India and South Korea [ [22] , [23] , [24] ]. In a study conducted by Maurya et al , multidrug-resistant TB was observed in 13.4% of EPTB cases in India [ 25 ].…”
Section: Discussioncontrasting
confidence: 77%
“…Previous studies have also noted that concurrent PTB-EPTB patients [9,10]. Boonsarngsuk et al [9]. demonstrated that 12.2% were of concurrent PTB-EPTB(120/986).…”
Section: Discussionmentioning
confidence: 92%
“…Tuberculous pleurisy is thought to represent primarily a hypersensitivity reaction to tuberculous protein [21]. Previous studies have also noted that concurrent PTB-EPTB patients [9,10]. Boonsarngsuk et al [9].…”
Section: Discussionmentioning
confidence: 99%